Congenital neutropenia with retinopathy, a new phenotype without intellectual deficiency or obesity secondary to VPS13B mutations. Issue 2 (5th December 2013) - Gueneau, Lucie; Duplomb, Laurence; Sarda, Pierre; Hamel, Christian; Aral, Bernard; Chehadeh, Salima El; Gigot, Nadège; St‐Onge, Judith; Callier, Patrick; Thevenon, Julien; Huet, Frédéric; Carmignac, Virginie; et al.
ABSTRACT Over one hundred VPS13B mutations are reported in Cohen syndrome (CS). Most cases exhibit a homogeneous phenotype that includes intellectual deficiency (ID), microcephaly, facial dysmorphism, slender extremities, truncal obesity, progressive chorioretinal dystrophy, and neutropenia. We report on a patient carrying two VPS13B splicing mutations with an atypical phenotype that included microcephaly, retinopathy, and congenital neutropenia, but neither obesity nor ID. RNA analysis of the IVS34+2T_+3AinsT mutation did not reveal any abnormal splice fragments but mRNA quantification showed a significant decrease in VPS13B expression. RNA sequencing analysis up‐ and downstream from the IVS57+2T>C mutation showed abnormal splice isoforms. In contrast to patients with typical CS, who express only abnormal VPS13B mRNA and truncated protein, a dose effect of residual normal VPS13B protein possibly explains the incomplete phenotype in the patient. This observation emphasizes that VPS13B analysis should be performed in cases of congenital neutropenia associated with retinopathy, even in the absence of ID, therefore extending the VPS13B phenotype spectrum. © 2013 Wiley Periodicals, Inc.